Effects of methiopropamine on cognitive function and monoaminergic systems in mice - Mohd Khairulanwar Bunaim; Nor syafinaz Yaakob; Hanafi Ahmad Damanhuri; hui-Yin Yow; Fadhlullah Zuhair Japar sidik; Norizal Mohd Noor; Norazrina azmi (Drug anD ChemiCal ToxiCology, 2025)
Methiopropamine (MPa), a novel psychoactive substance (NPs) similar to methamphetamine (Meth), warrants investigation into its neurotoxic effects on cognitive function and behaviors due to limited existing research. therefore, this study aimed to explore the effects of MPa on several behavioral parameters in mice, brain levels of monoamine neurotransmitters, and p-eRK1/2 expression. Mice were randomly divided into four groups (n = 10) which received daily intraperitoneal injections of either saline, 1 or 3 mg/kg of MPa, or 1 mg/kg of Meth for 7 days. the novel object recognition test (NORt) revealed a significant decline in recognition memory, particularly evident at a dose of 3 mg/kg of MPa, similar to Meth at 1 mg/kg, observed 24 h post-withdrawal. MPa at 3 mg/kg also impaired working and reference memory performance in the 8-arm radial maze (8-aRM) test and exhibited an anxiolytic effect in the open field test (OFt). these cognitive impairments were accompanied by decreased dopaminergic parameters and p-eRK1/2 expression within the prefrontal cortex (PFc). this further suggests that MPa neurotoxicity is targeted at the dopaminergic transmission in the PFc. in conclusion, MPa consumption is associated with memory impairment, which is attributable to dopaminergic deficits and reduced p-eRK1/2 activities in the PFc.